Disenfranchisement and blessedness: a reading of the Hagar and Ishmael story in the context of the Shona and Muslim communities of Zimbabwe: a liberation approach - Mwandayi, Canisius; Bayram, Ayla (School of Mission and Theology, 2016)
The article focuses on the Hagar and Ishmael story in the context of the Shona and Muslim communities of Zimbabwe. It seeks to apply the muslim communities of Zimbabwe to the story of Hagar and Ishmael against the background of an ill-treatment of either second wives or first wives and their children in both the shona and muslim communities. It states that the choice of these communities as a case study stems from the fact that both the communities allowed for polygamy as a value system.